2016
DOI: 10.3389/fncir.2016.00079
|View full text |Cite
|
Sign up to set email alerts
|

An Evolutionarily Conserved Mechanism for Activity-Dependent Visual Circuit Development

Abstract: Neural circuit development is an activity-dependent process. This activity can be spontaneous, such as the retinal waves that course across the mammalian embryonic retina, or it can be sensory-driven, such as the activation of retinal ganglion cells (RGCs) by visual stimuli. Whichever the source, neural activity provides essential instruction to the developing circuit. Indeed, experimentally altering activity has been shown to impact circuit development and function in many different ways and in many different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 122 publications
0
41
0
Order By: Relevance
“…Anamniotes, which include fish and amphibians, develop exclusively externally which allows for neuronal activity driven by the natural visual scenery (see review in this special topic issue by Pratt et al, 2016). Unlike fish and frogs, amniotes are hidden behind thick shells or develop in utero , which leads to a general deprivation of visual experience during the time when visual circuit refinement takes place.…”
Section: In the Absence Of Sensory Input Correlated Spontaneous Fmentioning
confidence: 99%
“…Anamniotes, which include fish and amphibians, develop exclusively externally which allows for neuronal activity driven by the natural visual scenery (see review in this special topic issue by Pratt et al, 2016). Unlike fish and frogs, amniotes are hidden behind thick shells or develop in utero , which leads to a general deprivation of visual experience during the time when visual circuit refinement takes place.…”
Section: In the Absence Of Sensory Input Correlated Spontaneous Fmentioning
confidence: 99%
“…In the visual system of vertebrates, spontaneous activity generated both in the retina and in retinorecipient structures is critical for organizing early experience and facilitating the developmental refinement of neural circuitry (Pratt et al, 2016). However, spontaneous activity also places serious constraints on the normal processing of sensory stimuli by adding varying amounts of neural noise, and can therefore affect how the organism interacts with its environment.…”
Section: Introductionmentioning
confidence: 99%
“…Monocular visual experience disrupts visual avoidance behavior. Prior work demonstrated that bilateral visual experience induces plasticity in the tectal circuit and enhances visuomotor behavior (Pratt et al 2016;Ruthazer and Aizenman 2010;Shen et al 2014). We tested if we could use monocular visual experience to drive plasticity exclusively in the contralateral tectal circuit and whether this would interfere with visuomotor behavior.…”
Section: Resultsmentioning
confidence: 97%
“…Experience-dependent cellular and circuit changes that result from bilateral visual stimulation provided to tadpoles are well documented (Pratt et al 2016;Ruthazer and Aizenman 2010), including improvements in visual avoidance behavior, mentioned above (Liu and Cline 2016;Shen et al 2014). Visual experience promotes refinement of the topographic map (Ruthazer and Cline 2004), elaboration of tectal neuron dendrites (Sin et al 2002), retinotectal synaptogenesis (Aizenman and Cline 2007;Ruthazer et al 2006), neuronal excitability (Aizenman et al 2003), and development of excitatory and inhibitory circuitry underlying visual information processing (Pratt and Aizenman 2007;Pratt et al 2008).…”
Section: Introductionmentioning
confidence: 99%